The United States and China: Competition, Partnership and Containment - Ali Hussein, Haider; Taama, Amjad; Kadhim Abbas AL-Maeeni, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The United States and China have undergone many changes in their relationship in the past years, but in recent years, relations between them, reached many critical junctures, especially in trade, and other political and military fields It is well known, that no study of any problem of international relations is complete without studying its future possibilities, based on data and indicators of reality at all levels. From this perspective, this study aims to set future possibilities for the policy of the United States towards China, since the track and form of this policy can be important factors in determining the strategic dimensions of the international interaction process in its future dimension, and impact on the structure of the international system. The future possibilities of US policy toward China will undoubtedly determine the nature of relations between the two parties within its assumed timeframe. On this basis, the problem of study can be raised about how the future of US policy toward China can be studied, which leads to a set of questions. These centers on: what is the future track of American policy toward China? What are the driving factors for each possibility, whether it is cooperation, competition, conflict, or partnership? The statements and assumptions made by the basic theories in the field of international relations concerned, with an understanding and interpretation of cases of cooperation, competition and conflict, which remains conditional on a number of conditions.